2006
DOI: 10.2353/ajpath.2006.060079
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Activating Factor Is Crucial in Psoralen and Ultraviolet A-Induced Immune Suppression, Inflammation, and Apoptosis

Abstract: Psoralen plus UVA (PUVA) is used as a very effective treatment modality for various diseases, including psoriasis and cutaneous T-cell lymphoma. PUVA-induced immune suppression and/or apoptosis are thought to be responsible for the therapeutic action. However, the molecular mechanisms by which PUVA acts are not well understood. We have previously identified platelet-activating factor (PAF), a potent phospholipid mediator, as a crucial substance triggering ultraviolet B radiation-induced immune suppression. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
90
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 55 publications
5
90
1
1
Order By: Relevance
“…For example, Silva et al (38) showed that oxidized lipids, including PAF, induced the expression of a wide range of chemokines. Because of the critical role PAF plays in UV-induced immune suppression (14,15), it is tempting to speculate that PAF is driving UV-induced CXCL12 expression. Another possible CXCL12 trigger might be the multitude of cytokines released following UV exposure including IL-4, IL-10, and TNF (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Silva et al (38) showed that oxidized lipids, including PAF, induced the expression of a wide range of chemokines. Because of the critical role PAF plays in UV-induced immune suppression (14,15), it is tempting to speculate that PAF is driving UV-induced CXCL12 expression. Another possible CXCL12 trigger might be the multitude of cytokines released following UV exposure including IL-4, IL-10, and TNF (39).…”
Section: Discussionmentioning
confidence: 99%
“…This is perhaps not surprising when one considers the wide range of inflammatory mediators and cytokines that mast cells have been shown to produce (10). Indeed, many of the inflammatory mediators released by mast cells including, histamine (10,11), PGE 2 (12), serotonin (13), platelet-activating factor (PAF) (14,15) TNF, IL-4, and IL-10 (16) are critical mediators of UV-induced immunosuppression. Grimbaldeston et al (17) recently demonstrated that mast cell-derived IL-10 limits the skin pathology associated with contact dermatitis and chronic inflammation induced by UV exposure, again reinforcing the growing appreciation for the ability of mast cells to regulate inflammation and the immune response.…”
mentioning
confidence: 99%
“…UVB is immunosuppressive and facilitates progression of non-melanoma skin cancer, and it has been proposed 24 that PAF and/or PAF-like lipids mediate this systemic immune suppression via PAF-receptor-mediated IL-10 production. Moreover, topical psoralen + UVA-mediated keratinocyte cytotoxicity has been reported to be decreased in PAF-receptor deficient mice in comparison to wild-type counterparts 28 .…”
Section: Paf System and Uvrmentioning
confidence: 99%
“…PAF is produced by physical stress, including UV light and trauma (14). PAF is involved in UVB, psoralen plus UVA light, and jet fuel-induced immune suppression (13,15,16). PAF also plays a role in regulating the immune response to microbial pathogens (14).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%